Cation effect on the (PEG 8000+sodium sulfate) and (PEG 8000+magnesium sulfate) aqueous two-phase system: Relative hydrophobicity of the equilibrium phases - Kamila Wysoczanska (2015)
The partitioning of four dinitrophenylated (DNP-) amino acids in aqueous two-phase systems of (polyethylene glycol (PEG)-8000 + sodium sulfate) and (polyethylene glycol (PEG)-8000 + magnesium sulfate) in five different tie-lines was experimentally determined at T = 298.15 K. The Gibbs energy of transfer of a methylene group between the two phases was calculated from the measured partition coefficients. This characterizes the relative hydrophobicity of the equilibrium phases. Values of Delta G*(CH2) were in range from (-0.674 to -1.012) kJ.mol(-1). A comparison of both systems was carried out. The results show that the cation type has a strong influence on the amino acids partitioning process. The largest relative hydrophobicity was noted for the ATPS system formed by sodium sulfate. This showed to be a better system for the separation.